THE IMPACT OF TRADE POLICIES ON AGRICULTURAL OUTPUT GROWTH IN SELECTED ARAB COUNTRIES FOR THE PERIOD 1990-2010 IRAQ AND SAUDI ARABIA, AMODEL - Lora AI-Saor (Mesopotamia Journal of Agriculture)
ABSTRACT The research aims to study and measure the impact of trade policies on the growth of agricultural output in some Arab countries, namely, (Iraq. Saudi Arabia) and adopted on the search a premise that the policies of trade hav different effects of varying the rate of financing agricultural output in the countries of the search sample, also adopted a search on the descriptive approach with the analysis quantification using multiple regression analysis. The search included a range of time series Twenty-one years (1990-2010). Were used method of least squares normal to see the impact of some economic indicators and agricultural independent variable approved financing agricultural output, and most important conclusions reached by the research is that the volume of agricultural imports exceeds the volume of agricultural exports, that features agricultural trade is negative during the period of the research. This reflects the level low capacity of the agricultural sector For both countries.  And show the results of the analysis also moral cultivation "(X1) for each of Iraq and Saudi Arabia, but for a variable agricultural exports (X2) has emerged not significant in its impact growth rate of agricultural output in both Iraq and Saudi Arabia, while the variable rate exposure economic agricultural (X3) has appeared in the moral influence on the growth of agricultural output in both countries, As for changing the relative importance of the surplus or deficit of the balance of payments to Total local output (X4) it has appeared in the moral influence on the growth of agricultural output in Iraq only and non Manuetha in Saudi Arabia  It has been found through analysis the lack of moral variable average real per capita income (X5) in both Iraq and Saudi Arabia, has also been reached to a set of findings and recommendations.